The Use of Miniature of Electric Power Line System In Electricity Distribution Network Subject At SMK Negeri 2 Banda Aceh - Muhammad Rizal Fachri; Malahayati Malahayati; Muhammad Zaki Fuadi (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
Students need to learn about power distribution networks in order to comprehend how electricity is distributed from its source to its consumers. However, many students lack interest and have trouble understanding the theory of distribution systems. The goal of this study is to develop a tiny teaching tool that will be used in Class XI of the Electrical Network Engineering Department at SMK Negeri 2 Banda Aceh to teach the concept of power distribution networks. The objective is to validate and assess the merits of employing small media while instructing students about power distribution systems. Data are gathered using an experimental methodology in this study and through validation, observation, documentation, and testing. The study's findings suggest that making small media for power distribution systems is appropriate for teaching. When compared to the pre-test score of 61.65, the final test results demonstrate a remarkable improvement, with an average post-test score of 90.00. Therefore, SMK Negeri 2 Banda Aceh's use of teaching materials utilizing tiny power distribution systems is very effective in improving students' learning outcomes in the subject of power distribution systems.